Socioeconomic factors associated with the perception of socioeconomic status among older adults in two Latin American countries - Brenes Camacho, Gilbert (2013)
The article´s main goal is to study the relationship between subjective perception of own economic situation and objective measures of economic well-being –sources of income, home ownership, education level, and informal family transfers– among the elderly in two Latin American countries: Mexico and Costa Rica.  The data come from two surveys about ageing: CRELES in Costa Rica and MHAS in Mexico.  The most important dependent variables is derived from the answer to the question “How would you rate your current economic situation? in Costa Rica, and “Would you say that your current economic situation is…?” in Mexico.  For both surveys, the answers were coded as a binary variable;  code 0 represents the Excellent, Very Good, and Good categories, while the code 1 represents the Fair or Bad categories. The analysis finds that retirement pension income is an important factor for defining self-rated economic situation in both countries.  In Costa Rica, spouse’s income and home ownership are relevant predictors for the perception of well-being, while in Mexico, receiving transfer income is associated with this perception.